Aberrant right subclavian artery: case report and literature review - Nasser, Michel; Petrocheli, Bruna Beatriz; Felippe, Thais Keltke Santos; Isola, Beatriz; Santos Pereira, Beatriz Caroline dos; Sartoreli, Ana Luiza Carvalho; Batista Junior, Joao Marques; Brandao, Gustavo Mucoucah Sampaio [UNESP] (Soc Brasileira Angiologia Cirurgia Vascular-sbacv, 2023)
The aberrant right subclavian artery, also known as the arteria lusoria, is the most common aortic arch anomaly, occurring in 0.5 to 1% of the population. There is a higher prevalence in women and it is usually associated with other anatomical variations, such as the non-recurrent laryngeal nerve, present in 86.7% of cases. In the majority of cases, the aberrant right subclavian artery causes no symptoms. We describe this anomaly in an 82-year-old, hypertensive, and asymptomatic patient who had undergone a thoracoabdominal angiography to investigate a chronic DeBakey type III aortic dissection with dilation of the descending aorta. The aberrant right subclavian artery followed a retroesophageal course and was associated with a Kommerell diverticulum. In view of its rarity, we conducted an integrative bibliographic review of literature from the last 6 years indexed on the Medline, UpToDate, Lilacs, Scielo, and Portal Capes databases and discuss the most frequent anatomical changes, symptomatology, and therapeutic management adopted.
Keywords: aberrant right subclavian artery; vascular anomaly; Kommerell diverticulum; arteria lusoria